2021
DOI: 10.1503/jpn.200091
|View full text |Cite
|
Sign up to set email alerts
|

Reduced visual contrast suppression during major depressive episodes

Abstract: Background: Previous studies have suggested that processing of visual contrast information could be altered in major depressive disorder. To clarify the changes at different levels of the visual hierarchy, we behaviourally measured contrast perception in 2 centre-surround conditions, assessing retinal and cortical processing. Methods: As part of a prospective cohort study, our sample consisted of controls (n = 29; 21 female) and patients with unipolar depression, bipolar disorder and borderline personality dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…Perception tests, for instance, could be used like a supplement to other methods of evaluating the efficacy of various medications as the treatment continues. However, because the experiential changes remain modest and demonstrated specifically when matching among sets, depression cannot be recognised by assessing visual perception [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perception tests, for instance, could be used like a supplement to other methods of evaluating the efficacy of various medications as the treatment continues. However, because the experiential changes remain modest and demonstrated specifically when matching among sets, depression cannot be recognised by assessing visual perception [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals with depression exhibit 'depressive realism' [88] in which they exhibit more accurate ratings than individuals without depression about their control over outcomes in an experiment [89]. Enhanced accuracy in depression is further documented by reduced susceptibility to visual illusions [90]. In addition, similar to individuals with ASD, depressed individuals display a diminished or absent optimism bias, meaning that they integrate information objectively, regardless of whether the information is desirable or undesirable [91].…”
Section: Box 3 Enhanced Rationality In Other Clinical Disorders?mentioning
confidence: 99%
“…Indeed, many lines of studies have reported that MDD is often associated with the subjective experience of altered visual perception, such as photophobia, perceived dimness and reduced visual contrast discrimination ( 49 51 ). Moreover, the impairment in visual perception was found to be directly related to the psychopathological symptoms of MDD ( 4 , 8 ). In our study, we found PPS, as indicated by amplitude ratios (A2s/A1), was significantly related to the symptom severity of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the cortical processing of different types of visual perceptions in MDD patients, such as visual motion, visual contrast and visual integration, using psychophysical measures. The results revealed higher motion suppression ( 3 ), decreased contrast suppression ( 4 ) and deficits in integration of visual inputs in MDD ( 5 ). The psychophysical deficits in visual perception in MDD are closely related to the abnormality of biochemical changes in the occipital cortex.…”
Section: Introductionmentioning
confidence: 96%